Chiral Nanoparticle as a New Efficient Antimicrobial Nanoagent. Issue 4 (27th December 2016) - Xin, Qi; Liu, Qian; Geng, Lingling; Fang, Qiaojun; Gong, Jian Ru
Abstract : d ‐type functionalized nanoparticles (NPs) can bind to MurD ligase with high affinity and inhibit its peptidoglycan synthetic enzyme activity, and finally cause bacterial killing. In contrast, its L‐type counterpart displays a negligible effect, indicating that the chiral structure of the functionalized NPs plays an essential role in their binding interaction with MurD and therefore the antibacterial activity.